Re: Simplifying algebraic expressions

*To*: mathgroup at smc.vnet.net*Subject*: [mg66929] Re: Simplifying algebraic expressions*From*: "Dana DeLouis" <ddelouis at bellsouth.net>*Date*: Sun, 4 Jun 2006 01:10:20 -0400 (EDT)*Sender*: owner-wri-mathgroup at wolfram.com

> (-1)^{2 x + 3 y} and be able to simplify to (-1)^y. Hi. Here's one idea: equ = (-1)^(2*x + 3*y); To get a feel for the equation: Reduce[2*x + 3*y == y, {x, y}] y == -x Therefore: Assuming[y == -x, Simplify[equ]] (-1)^y Looks like x & y can be complex as well. Here, 'x is complex... x = 3 + 4*I; And 'y is therefore... y = -x -3 - 4*I Your equation is: equ (-1)^(-3 - 4*I) Which is the same as: (-1)^y (-1)^(-3 - 4*I) -- HTH. :>) Dana DeLouis Mathematica 5.2 "Amitabha Roy" <aroy at cs.bc.edu> wrote in message news:e5mhis$kg3$1 at smc.vnet.net... > Hello: > > I would like Mathematica to be able to take an expression, say, > > (-1)^{2 x + 3 y} and be able to simplify to (-1)^y. > > Is there a way one can do this ? > > Thanks >